Nicotine’s impact on platelet function: insights into hemostasis mechanisms - Wu, Xiayu; Liu, Yongjun; Zou, Changhao; He, Fuqin; Guo, Fang; Liu, Sijia; Fan, Yi; Zhu, Xuedong; Zhou, Qianyi; Shu, Dan (Frontiers in Pharmacology, 2025)
IntroductionTraditional Miao and Dai Chinese medicines have used nicotine-rich leaf tobacco to treat traumatic injuries by promoting hemostasis. While nicotine is known to enhance platelet aggregation, its effects on other platelet functions and underlying mechanisms remain unclear.Methods and ResultsThis study aimed to thoroughly investigate nicotine’s effects on human platelets and its pharmacological mechanisms, using thromboelastography to assess nicotine’s impact on platelet function during coagulation. This study aimed to investigate the functional effects of nicotine on human platelets and elucidate its pharmacological mechanisms. The impact of nicotine on platelet function during the coagulation process was assessed using thromboelastography. Further studies showed that nicotine fully activates washed platelets, promoting aggregation, granule release, adhesion, spreading, and plaque retraction. Concurrently, nicotine was found to enhance the intracellular concentration of calcium ions in platelets ([Ca2+]i). To explore the underlying mechanisms, molecular docking software was employed to identify the platelet membrane receptors PAR1 and PAR4, which exhibited the highest docking scores with nicotine. Intervention with two receptor inhibitors demonstrated that only the PAR4 inhibitor could reverse the stimulatory effects of nicotine on platelet granule release. Through the examination of alterations in the downstream signaling pathways of PAR4 receptors, it was determined that nicotine promo-facilitates the phosphorylation of PI3K, AKT, and ERK1/2 proteins, subsequently contributing to the activation of αIIbβ3 receptors in platelets. Conversely, the application of PAR4 inhibitors was found to reverse these effects.DiscussionIn conclusion, nicotine activates αIIbβ3 receptors and significantly enhances platelet function by promoting the phosphorylation of the platelet PAR4 receptor signaling pathway. These findings suggest the potential utility of nicotine as a hemostatic agent.